Efektivitas Pengelolaan Administrasi Akademik Fakultas Syari’ah IAIN Ar-Raniry Banda Aceh - Maqfirah Maqfirah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2013)
Administration is an important element in achieving organizational objectives. Administration is a management process that can be implemented in any educational activities, both in the planning, organizing, mobilization, coordination, direction and control. This study uses descriptive qualitative approach. The technique of collecting data through observation, interviews and documentation, research subjects is Dean of the Faculty of Sharia, Assistant Dean for Academic Affairs, Head of the Administration Field Equipment, Academic Head of sub-section along with staff. The results showed that 1) Planning course academic activities can be seen from the course management system using a system of credits, setting the course schedule, the division of tasks lecturer, and documentation of student values, 2) Implementation of academic management program has been running but not maximum, 3) constraints obstacles encountered in the management of academic administration include: lack of academic personnel, inadequate facilities and infrastructure. Implementation that does not comply with the plan because of non-availability of professional academic and support facilities. Abstrak Administrasi merupakan unsur penting dalam mewujudkan pencapaian tujuan organisasi. Administrasi merupakan proses pengelolaan yang dapat diimplementasikan dalam setiap kegiatan pendidikan, baik dalam perencanaan, pengorganisasian, penggerakan, pengkoordinasian, pengarahan dan pengawasan. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data melaui mobservasi, wawancara dan studi dokumentasi, subyek penelitian adalah Dekan Fakultas Syari’ah, Pembantu Dekan Bidang Akademik, Kabag Tata Usaha Bidang Perlengkapan, Kasubbag Akademik beserta Staf. Hasil penelitian menunjukkan bahwa 1) Perencanaan program kegiatan akademik dapat dilihat dari sistem pengelolaan perkuliahan dengan menggunakan sistem SKS, pengaturan jadwal kuliah, pembagian tugas dosen, dan dokumentasi nilai mahasiswa, 2) Pelaksanaan program pengelolaan akademik telah berjalan namun belum maksimal, 3) Hambatan-hambatan yang dijumpai dalam pengelolaan administrasi akademik meliputi: terbatasnya tenaga akademik, sarana dan prasarana belum memadai. Pelaksanaan yang tidak sesuai dengan perencanaan karena keterbatasan tenaga akademik yang profesional dan fasilitas pendukung. Kata Kunci: Efektivitas, pengelolaan, dan administrasi akademik.